Integrating stakeholder's role in mitigating risks for future cleaner production - Ngan, Sue Lin (Animo Repository, 2018)
Risk assessment and management has gained high interest in recently year, both in research field and business arena. It is mainly due to the advancement of information technology, amelioration of big data for artificial intelligence which made precaution more plausible and viable. With global movement to shift to cleaner production system, it also spurs up the development and adoption of various risk assessment and analysis tools that cater cleaner production project’s profile. As cleaner production system and infrastructures often engaged with high upfront cost, effective risk management and mitigations is deemed necessary to secure the high investment cost. Different methods have been proposed and developed in the past to diagnose and analyse potential risk events to recommend mitigation strategies. However, there is considerably less works incorporating the role of stakeholders in managing and mitigating risks. Every stakeholder plays different and yet crucial roles in the development of an industry, and each with their own strengths and weaknesses. It is imperative for the stakeholders to understand and uptake its strength in mitigating risk to avoid a waste of resources and efforts to act beyond their capability or power of influences. In this work, fuzzy analytical network process (FANP), and Decision Making Trial and Evaluation Laboratory (DEMATEL) are adopted to develop a hybrid model to evaluate risk mitigation strategies based on the role of industry stakeholders. The outer-dependency of the role of stakeholders and risk mitigation strategies are derived by pairwise comparison questionnaires of FANP with linguistic scale. On the other hands, the interdependency (i.e. dependency power, influence power) of the role of stakeholders and risk mitigation strategies are evaluated with DEMATEL. The outputs from FANP and DEMATEL are then combined with the composition of supermatrix to select the most effective mitigation strategy. This method provides a systematic way to incorporate the role of different stakeholders in enhancing the overall effectiveness of mitigation strategies.